NALISIS BIBLIOMETRIK TREND PENELITIAN KOLEKSI SKRIPSI S1 KEPERAWATAN MENGGUNAKAN SOFTWARE VOSVIEWER DI PERPUSTAKAAN ITSKES ICME JOMBANG - Dwi Nuriana; Ayu Wulansari; Sigit Dwi Laksana (Pustabiblia: Journal of Library and Information Science, 2025)
In the era of digital transformation and scientific advancement, the thesis is one of the academic requirements that must be completed by students of the Bachelor (S1) program, a scientific product that is in accordance with the peculiarities of the S1 Nursing study program with the characteristics of an emergency. This study aims to analyze the thesis titles of S1 Nursing students at ITSKes Insan Cendekia Medika Jombang in 2023– 2025 with a bibliometric approach using VOSviewer software. The background of this research is based on the gap between the topic of the student's thesis and the peculiarities of the study program that emphasizes the field of emergency nursing. The research method used is quantitative descriptive with co-word, co-occurrence, and citation analysis techniques. The data used came from 177 titles of student final projects obtained from institutional repositories, data was analyzed through three types of visualizations in VOSviewer, network, density, and overlay visualization.The results of the study show that the dominant topics in students' theses revolve around community nursing and general issues such as stress, sleep quality, nutritional status, hypertension, and adolescent and elderly behavior. Emergency topics such as trauma, triage, resuscitation, and disaster management appear only very limited, both in keywords and abstract content. The VOSviewer visualization shows an imbalance in the distribution of themes, suggesting that the main focus has not yet reflected the peculiarities of the study program. The conclusion of this study is that student research trends are not fully in line with the vision, mission, and scientific characteristics of the S1 Nursing study program that is oriented towards emergency nursing. Therefore, academic strategies are needed such as topic briefings by supervisors and library officers who can provide recommendations for research topics in accordance with the characteristics of the study program, as well as the preparation of superior topic policies based on bibliometric analysis.